Chapter Tempi duri per la storia. Il contributo della Public History of Education alla consapevolezza delle nostre complesse identità - Bandini, Gianfranco (Public History of Education. Teorie, esperienze, strumenti, 2022)
In the educational training pathway, the history of education is usually present. From the moment of recruitment onwards, however, the interest in a historical approach disappears completely, and teachers tend to focus on the current challenges of their work.